Peran Guru Akidah Akhlak dalam Internalisasi Nilai Moderasi Beragama pada Siswa Kelas IX MTs Al-Washliyah 48 Binjai - Nurmala Sari; Rahmi Utami (Universitas Islam Negeri Sumatera Utara Medan, 2026)
Religious moderation is essential in Indonesia’s plural society to foster tolerant and inclusive generations. This study aims to analyze the role of Akidah Akhlak teachers in internalizing the values of religious moderation among ninth-grade students at MTs Al-Washliyah 48 Binjai. This research uses a qualitative approach with a case study design involving Akidah Akhlak teachers and ninth-grade students. Data were collected through semi-structured interviews, participatory observation, and documentation, and analyzed using the Miles and Huberman interactive model. The results show that teachers play an active role through contextual learning, role modeling, habituation, and dialogical teaching strategies. These strategies are integrated with values of tolerance, justice, equality, cooperation, empathy, openness, and unity, and are implemented through discussions, case studies, role-playing, and storytelling methods. It can be concluded that Akidah Akhlak teachers play a significant role in strengthening students’ understanding and practice of religious moderation, although challenges such as family influence, social media exposure, and limited instructional time still exist.